Exploration and Analysis of Titanium Oxide Nanomaterials Using Scanning Electron Microscopy and Energy Dispersive Spectroscopy - Owolabi, Joseph; Ojadi, Pius (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
This research study delves into the synthesis and comprehensive characterization of TiO2 nanomaterials using the sol-gel method. Thorough material property determination is essential before integrating substances into diverse fields such as Science, Engineering, and Technology. This study focuses on the synthesis of titanium oxide nanoparticles via the sol-gel technique employing Titanium Tetra chloride (TiCl4) and Ethanol (CH3CH2OH) as precursor materials at ambient temperature. The resultant gel was subjected to calcification at 600°C for one hour, and subsequent characterization was performed using Scanning Electron Microscopy (SEM) with a JEOL JSM-7600F model, as well as Elemental Dispersion Spectroscopy (EDS). The findings reveal the prevalence of the Anastasia phase within the TiO2 antiparticles, a highly valuable state for various applications. Electron micrographs of the titanium oxide nano particles portray delicate, aggregate, and fiber-like structures. EDS analysis attests to the composition, with Titanium and Oxygen elements constituting 70.24% and 20.30% of the total weight, respectively, indicating a composition ally pure sample comprising 90.54% of the analyzed components. Detected as impurities, carbon and silicon are present in trace amounts, contributing 6.24% and 3.23% by weight, respectively, culminating in an impurity content of 9.46%. The significance of the Anastasia variant of titanium oxide extends to diverse applications, including but not limited to lithium-ion batteries, filtration systems, anti-reflective coatings, and various environmental uses. Furthermore, this nanomaterial exhibits promise in ultraviolet (UV) screening agents like sunscreens, and sunglasses, and serves as a preservative in food packaging applications. This research offers a comprehensive understanding of the synthesis process, material characteristics, and potential utility of Anastasia titanium oxide nanomaterials in numerous practical applications.